Thrombus remodelling by reversible and irreversible P2Y12 inhibitors. (31st December 2023) - Tunströmer, Kjersti; Faxälv, Lars; Larsson, Pia; Lindahl, Tomas L.; Boknäs, Niklas
Abstract: Pharmacological inhibition of the platelet ADP-receptor P2Y12 is a cornerstone in the prevention of atherothrombotic events in adult patients with acute coronary syndrome (ACS). Thienopyridines such as clopidogrel and prasugrel exert their antithrombotic effect by means of active metabolites that irreversibly inhibit P2Y12 . Due to the short half-life of these metabolites, a subpopulation of ADP-responsive platelets will form in between dosing. With increased platelet turnover rate or poor patient compliance, the fraction of ADP-responsive platelets will increase, potentially increasing the risk for new thrombotic events. In contrast, the reversible P2Y12 inhibition produced by direct-acting ADP blockers such as ticagrelor and cangrelor inhibit the entire platelet population. In this study, we evaluated the impact of these pharmacological differences on thrombus formation in an ex vivo flow chamber model. A customized image analysis pipeline was used for automatized, large-scale identification and tracking of single platelets incorporated into the thrombus, enabling quantitative analysis of the relative contribution of inhibited and uninhibited platelets to thrombus growth and consolidation. Comparative experiments were conducted using the irreversible and reversible P2Y12 inhibitors prasugrel active metabolite (PAM) and ticagrelor, respectively. Our results show that PAM inhibited thrombus platelet recruitment more gradually than ticagrelor, with a slower onset of inhibition. Further, we show that the presence of a small fraction (<10%) of uninhibited platelets did not abrogate the antithrombotic effect of PAM to any significant extent. Finally, we demonstrate a gradual enrichment of inhibited platelets in the thrombus shell due to selective recruitment of inhibited platelets to the thrombus periphery.